Mechanism of Artificial Heart - Yamane, Takashi; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2016)
This book first describes medical devices in relation to regenerative medicine before turning to a more specific topic: artificial heart technologies. Not only the pump mechanisms but also the bearing, motor mechanisms, and materials are described, including expert information. Design methods are described to enhance hemocompatibility: main concerns are reduction of blood cell damage and protein break, as well as prevention of blood clotting. Regulatory science from R&D to clinical trials is also discussed to verify the safety and efficacy of the devices.
Introduction -- What kinds of artificial heart are available? -- How do we select pump types? -- Selection of bearing types: Key to durability -- Motor, battery, and magnetic suspension -- Flow visualization and computational fluid dynamic analysis -- How do we select materials? -- Enhancement of hemocompatibility -- System evaluation -- Remarks and future aspects.
Keywords: Biomedical engineering; Engineering design; Heart -- Surgery; Control engineering; Robotics; Automation; Biomedical Engineering and Bioengineering; Engineering Design; Cardiac Surgery; Control, Robotics, Automation